(untitled) (New Jesey, NJ, 2002)
This is the fourth conference on "Supersymmetry and Perturbation Theory" (SPT 2002). The proceedings present original results and state-of-the-art reviews on topics related to symmetry, integrability and perturbation theory, etc.
Keywords: Symmetry (Physics),Perturbation (Mathematics); Cấu trúc cân đối (Vật lý),Trạng thái (Toán học)